Factors affecting mothers’ satisfaction with expressive and creative therapy provided to adolescents with learning disabilities: self-efficacy, stress and duration of therapy - Abramovski, Gal (Advances in Social Sciences Research Journal, 2020)
In view of the paucity of evidence on satisfaction with expressive and creative therapy among mothers to adolescents with learning disability in the context of special education schools, the present study examined the relationship between mothers’ satisfaction with therapy and two psychological measures – self-efficacy and stress. Satisfaction was also examined in relation to duration of therapy. The sample comprised 54 mothers to adolescents with LD who were in therapy for at least one year. Data was collected via five structured questionnaires. The findings reveal that satisfaction with therapy in general was positively related to mothers’ self-efficacy and negatively related to level of stress, whereas perceived effectiveness of therapy was not related to the two psychological measures. Duration of therapy, on the other hand, was positively related to perceived effectiveness of therapy but not related to satisfaction with therapy in general. The theoretical implications of the results and their practical implications for expressive and creative therapy within schools are discussed.